The Influence Of Organizational Support And Job Characteristics On Service Quality Through Innovation As An Intervening Variable - Opi Muzalifah; Widodo Sunaryo; Mohammad Entang (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This Research Aims To Identify And Determine Efforts That Can Be Made To Improve Service Quality Through A Study of its relationship with Organizational Support, Job Characteristics and Innovation. The population of this study was 161 implementing employees at the Bogor Regency Food Crops, Horticulture and Plantation Service with a sample size of 115 people, whose determination used the Slovin formula with an error tolerance of 5%. Data was obtained using instruments in the form of questionnaires and analyzed using descriptive and inferential statistical analysis. The results showed seven positive and significant relationships. First, there is a positive and significant direct relationship between the variables Organizational Support and Innovation with a correlation coefficient of 0.347. Second, there is a positive and significant direct relationship between Job Characteristics and Innovation with a correlation coefficient value of 0.254. Third, there is a positive and significant direct relationship between Organizational Support and Service Quality with a correlation coefficient of 0.102. Fourth, there is a positive and significant direct relationship between Job Characteristics and Service Quality with a correlation coefficient value of 0.087. Fifth, there is a positive and significant direct relationship between Innovation and Service Quality with a correlation coefficient of 0.389. Sixth, there is a positive and significant indirect relationship between Organizational Support and Service Quality through Innovation with a correlation coefficient of 0.084. Seventh, there is a positive and significant indirect relationship between Job Characteristics and Service Quality through Innovation with a correlation coefficient of 0.104.